The crusades - Jaspert, Nikolas (Routledge, 2006)
With a long chronological span, from the eleventh to the late fifteenth century and with a geographical coverage of the whole of Europe and some of the Middle East, Nikolas Jaspert presents a clear and concise introduction to the history of the Crusades.